Report on industrial attachment with Singapore Institute of Manufacturing Technology - Wong, Kathy Pooi Wen (2015)
The main focus of these 20 weeks of Industrial Attachment (IA) at SIMTech was on three main projects, namely design and development of portable colorimeter for microfluidics applications, design and development of cell incubator for microfluidics application and the implementation of quality system to the attached programme according to ISO 13485 requirements. These three projects were at different phases respectively in these 20 weeks of involvement.